(untitled) (Third Sector Social Economic Review, 2024)
Many natural, human and technological disasters occur in the world. Disasters and crises have always been a matter for public administration to find solutions. Each country has its own institutional structure and a perspective on disaster management. Comparative evaluation of the systems of countries is important to find the best management approach. This article compares the Disaster and Emergency Presidency (AFAD), the organization responsible for disaster management in Turkey, with the Federal Emergency Management Agency (FEMA), the organization responsible for disaster management in the United States of America. In this framework, the characteristics of the disaster management system in both countries are revealed and the similarities and differences between them are discussed. It is evaluated that there is no planning in the formation of the disaster and emergency systems of Turkey and the USA, and the events that occur determine the formation and course of the system. In an unconscious and uncoordinated environment, the size of the disaster will change and may cause greater destruction. In this context, this study examines how the current systematic structure is formed in Turkey and the USA in disasters and emergencies, and what kind of a path is followed before and after the disaster management stages through AFAD and FEMA. As a result, disaster management systems of two different countries are compared, their positive and negative aspects are indicated and the importance of reaching a successful disaster management system is emphasized.